RANCANG BANGUN SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN DI FAKULTAS TEKNIK UNIVERSITAS LAMBUNG MANGKURAT - Maya Amalia; Muhammad Alkaff; Yuslena Sari (Jurnal Teknologi Informasi Universitas Lambung Mangkurat (JTIULM), 2016)
Implementation of management information sistems in state institutions or public organizations, will allow it to manage a variety of data needed to be valuable information for both internal organization and for those who are outside the organization. Faculty of Engineering, University Mangkurat in this case still has shortcomings in performing data collection associated with educators and education personnel, mainly deals with research and community service. The data collection process at the Faculty of Engineering, University Mangkurat still done manually and not computerized. The design and construction of a sistem of personnel information would be very helpful in speeding up the process of collection of data pertaining to educators and education personnel. Hopefully, by the information sistem, data educators and educational staff in the Faculty of Engineering, University of Mangkurat can be neatly arranged so as to facilitate the implementation of monitoring and evaluation in the field of personnel.